Potential role of inoculum size in biomass accumulation and antioxidant secondary metabolites production in adventitious root cultures of Stevia rebaudiana - Ahmad, Naveed; Ahmad, Nisar; Sajid, Muhammad; Rauf, Kamran; Iqbal, Mudassar; Numan, Muhammad; Ullah, Irfan; Khan, Amir; Al-Qahtani, Wahidah H.; Abdel-Maksoud, Mostafa A.; AbdElgawad, Hamada; Iqbal, Babar; et al. (Springer Nature, 2025)
The present study aimed to investigate the effect of initial inoculum size on adventitious root growth and secondary metabolite production in Stevia rebaudiana s root cultures, using various initial inoculum sizes (0.5, 1.0, 1.5, and 2.0 g). The roots were collected from the in-vitro seed-derived plantlets and transferred to a half-strength MS medium with 0.5 mg l−1 naphthalene acetic acid (NAA) to establish adventitious root cultures. Growth kinetics and fresh and dry biomass of adventitious root cultures were enhanced with inoculum size from 0.5–2.0 g. Adventitious root cultures did not show lag phases however, the growth curve was increased at an early stage (day 3) of log phases and sustained for 27 days of culture. The fresh and dry biomass accumulations of the adventitious root cultures were increased by 51 and 120% with 1.5 g inoculum size as compared to a smaller inoculum size (0.5 g). Adventitious root cultures at an initial inoculum size of 2.0 g had a significantly higher content of total phenolics (TPC; 41.46 mg g−1 DW), total flavonoids (TFC; 33.44 mg g−1 DW), and around 98.82% higher potential for scavenging free radicals. In addition, the initial inoculum size of 1.5 g was observed with higher dulcoside contents (0.71 mg g−1 DW), and an inoculum size of 1.0 g was noted with higher content of stevioside (64.75 mg g−1 DW) and rebaudioside (29.67 mg g−1 DW). Therefore, it is concluded that adventitious root cultures accumulated greater fresh and dry biomasses at an inoculum size of 1.5 g, a higher amount of TPC, TFC, and DRSA at 2.0 g, and stevioside and rebaudioside contents at 1.0 g.
Keywords: Adventitious root; anioxidant; inoculum; rebaudioside; Stevia rebaudiana; stevioside